Virtualización de las funciones de red (NFV) y las redes definidas por software (SDN) en la infraestructura de comunicaciones - Proaño Solórzano, Pedro Pablo (2023)
The present work was carried out with the purpose of developing a teaching manual that integrates the virtualization of network functions (NFV) and software-defined networks (SDN) in the UDIV laboratories of infrastructure for student learning in the Computer career. For this project it was necessary to use EDER, which was adapted to the type of research proposed and allowed us to achieve the objective proposed in the research. In the study phase, the requirements of the UDIV were analyzed, in the next stage the characteristics and components of the different software options were analyzed and evaluated in detail. In the execution, starting from the design of the solution, it was implemented based on the architecture proposed for the development and execution of the NFV and SDN functions, and in the review it was possible to provide network resources to improve performance, flexibility and capacity. file recovery on a network. With the results obtained from the implementation of these new technologies, the researchers developed a teaching manual addressing its development step by step, to serve as a teaching tool where students acquire both theoretical and practical knowledge in this field. Since it is important to be at the same level in terms of knowledge of new technologies and their accelerated development, it is necessary to generate advanced knowledge on computer network issues.